2005
DOI: 10.1029/2005ja011179
|View full text |Cite
|
Sign up to set email alerts
|

Pi2 pulsations in a small and strongly asymmetric plasmasphere

Abstract: [1] We study a Pi2 pulsation that occurred at $1520 UT on 29 August 2000. This Pi2 event was observed at ground stations from high (geomagnetic latitude $65°) to low latitudes ($17°) near midnight with an identical waveform and oscillated with a frequency of $11 mHz. During the event, a global image of the plasmasphere was obtained from the IMAGE satellite, and the location of the plasmapause was clearly identified. The plasmasphere was small and strongly asymmetric in longitude. The plasmapause was located at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…For example, Kim et al (2005b) reported a significant mismatch between the frequency of an observed Pi2 (11 mHz) and the PCR frequency (28 mHz) estimated using (1) for a realistic V Aeq profile in the magnetosphere derived by Denton et al (2006). Even with the assumption of a larger radial distance of the effective outer boundary in consideration of a possible extension of the mode beyond the plasmasphere (the PVR effect, Sect.…”
Section: Periodmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Kim et al (2005b) reported a significant mismatch between the frequency of an observed Pi2 (11 mHz) and the PCR frequency (28 mHz) estimated using (1) for a realistic V Aeq profile in the magnetosphere derived by Denton et al (2006). Even with the assumption of a larger radial distance of the effective outer boundary in consideration of a possible extension of the mode beyond the plasmasphere (the PVR effect, Sect.…”
Section: Periodmentioning
confidence: 95%
“…2.2), the model frequency was higher than the observed frequency. Although Kim et al (2005b) favored a BBF model for their particular Pi2 event (see Sect. 3.3 for more discussion on the BBF-driven mechanism), caution is in order regarding the mass density estimates employed by the model (see below for additional comments).…”
Section: Periodmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Lester et al [], the SCW model is reasonably successful at explaining middle‐latitude magnetic bay structures and the orientations of the major axes of Pi2 hodograms, although the model oversimplifies substorm onset currents. The SCW model for Pi2 pulsations is presently accepted as useful for determining the approximate locations of the upward/downward field‐aligned currents (FACs) of SCW systems [e.g., Kitamura et al , ; Kim et al , ]. However, some unsolved questions remain regarding the SCW model for Pi2 pulsations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus these researchers concluded that the Pi2 period is determined by the temporal structure of BBF. Kim et al [2005a] examined a Pi2 pulsation when the plasmasphere becomes small and highly asymmetric. They concluded that this Pi2 pulsation is unlikely to be caused by the cavity mode and is expected to be associated with BBFs.…”
Section: Introductionmentioning
confidence: 99%